2021
DOI: 10.1038/s41419-021-03402-7
|View full text |Cite|
|
Sign up to set email alerts
|

The androgen receptor/filamin A complex as a target in prostate cancer microenvironment

Abstract: Prostate cancer represents the major cause of cancer-related death in men and patients frequently develop drug-resistance and metastatic disease. Most studies focus on hormone-resistance mechanisms related to androgen receptor mutations or to the acquired property of prostate cancer cells to over-activate signaling pathways. Tumor microenvironment plays a critical role in prostate cancer progression. However, the mechanism involving androgen/androgen receptor signaling in cancer associated fibroblasts and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 72 publications
1
67
0
Order By: Relevance
“…CM was collected and centrifuged, while the cells were detached by trypsin and counted. CM was normalized to 1 × 10 6 MDA-MB-231 cells and MMP-9 proteolytic activity was assayed in CM as reported ( Di Donato et al, 2021 ). It appeared as a clear band migrating at ≈92 kDa on a blue background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CM was collected and centrifuged, while the cells were detached by trypsin and counted. CM was normalized to 1 × 10 6 MDA-MB-231 cells and MMP-9 proteolytic activity was assayed in CM as reported ( Di Donato et al, 2021 ). It appeared as a clear band migrating at ≈92 kDa on a blue background.…”
Section: Methodsmentioning
confidence: 99%
“…Spheroids were generated as reported ( Di Donato et al, 2021 ). MDA-MB-231 and MDA-MB-453 cells (3 × 10 4 ) were mixed in each well with 250 μl of phenol red-free growth factor-reduced Matrigel (10 mg/ml; BD Biosciences) and 50 μl of spheroid plating medium.…”
Section: Methodsmentioning
confidence: 99%
“…The phosphorylated p27 at Ser 10 was stabilized and attributable to cell cycle arrest at G0/G1 of fibroblasts (Castoria et al, 2014). Meanwhile, the AR/FlnA complex also triggered the activation of focal adhesion kinase FAK, Rac1, and paxillin via recruiting integrin beta 1, promoting cell migration of NIH3T3, HT1080 cells, and PCa-derived fibroblasts (Castoria et al, 2011;Di Donato et al, 2021). These findings suggest the therapeutic value of targeting the AR/FlnA complex to suppress the malignant activity of CAFs.…”
Section: Interaction Between Androgen Receptor Signaling In Cancer-associated Fibroblasts and Prostate Cancermentioning
confidence: 86%
“…These CAFs are components of the tumor microenvironment playing crucial roles in tumor progression and treatment response [60,61]. Interesting approaches were developed by Di Donato et al [23]., where the prostate tumor growth was stimulated by androgen in co-cultures using CAFs derived from patients with positive AR (androgen receptor) and cell lines that were either AR positive or negative [23]. Bladder cancer progression, migration, and invasion were also shown to be triggered by factors secreted by CAFs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer progression, migration, and invasion were also shown to be triggered by factors secreted by CAFs [22]. In both cases, inhibiting CAF signaling sufficed to decrease tumor aggressiveness [22,23]. Although several studies indicated the influence of the microenvironment in response to chemotherapy, we selected only cells showing epithelial features (cells 2 and 3) to evaluate the treatment response since the selected drugs target the tumor cells and not the microenvironment.…”
Section: Discussionmentioning
confidence: 99%